Analisis Pengaruh Empowerment Leadership Terhadap Creative Problem Solving Dengan Mediasi Dynamic Exploration Capability Studi di PT. Casuarina Harnessindo Pemalang - Nugroho Wisnu Wardani (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
The purpose of this study was to determine the effect of Empowerment Leadership on Creative Problem Solving faced by employees and the role of Dynamic Exploration Capability.The population in this study were all employees of PT. Casuarina Harnessindo Pemalang. There were 150 samples, but 137 samples were processed. The analysis tool uses the Structural Equation Model (SEM).The results of empirical investigations prove that Empowerment Leadership has a significant positive effect on Dynamic Exploration Capability, and Dynamic Exploration Capability has a significant positive effect on Creative Problem Solving. While the hypothesis that Empoworment Leadership has a significant positive effect on Creative Problem Solving is rejected. The mediating role of Dynamic Capability is proven by the P-velue value being smaller than the 0.05 significance value